2012
DOI: 10.1038/ejhg.2012.274
|View full text |Cite
|
Sign up to set email alerts
|

Report of four new patients with protein-truncating mutations in C6orf221/KHDC3L and colocalization with NLRP7

Abstract: To date, two maternal-effect genes have been shown to have causative roles in recurrent hydatidiform moles (RHMs); NLRP7 that is mutated in 48-60% of patients with RHMs and C6orf221 (HUGO-approved nomenclature is now KHDC3L), a recently identified gene, that is mutated in 14% of patients with RHMs who are negative for NLRP7 mutations. We sequenced KHDC3L in 97 patients with RHMs and reproductive loss who are mostly negative for NLRP7 mutations. We identified three unrelated patients, each homozygous for one of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 30 publications
2
42
0
2
Order By: Relevance
“…NLRP7 is a major gene for recurrent HMs and is mutated in 48%–80% of patients, depending on patients’ ascertainment criteria and populations 20–23 . KHDC3L is a minor gene for recurrent HMs and is mutated in only 10%–14% of patients with no NLRP7 mutations 19 23 24. To date, approximately 47 different mutations have been reported in patients with two NLRP7 -defective alleles (http://fmf.igh.cnrs.fr/ISSAID/infevers/).…”
Section: Introductionmentioning
confidence: 99%
“…NLRP7 is a major gene for recurrent HMs and is mutated in 48%–80% of patients, depending on patients’ ascertainment criteria and populations 20–23 . KHDC3L is a minor gene for recurrent HMs and is mutated in only 10%–14% of patients with no NLRP7 mutations 19 23 24. To date, approximately 47 different mutations have been reported in patients with two NLRP7 -defective alleles (http://fmf.igh.cnrs.fr/ISSAID/infevers/).…”
Section: Introductionmentioning
confidence: 99%
“…Both genes were repeatedly seen to be responsible for recurrent hydatidiform moles (RHMs) [54][55][56][57][58][59][60][61]. Despite being diploid biparental, therefore with a normal biparental contribution to their genomes, RHM tissues lack maternal methylation marks on several maternally imprinted genes.…”
Section: Scmc Involvement In Epigenetic Reprogramming Of Zygotesmentioning
confidence: 99%
“…While approximately 75% of pregnancies in women with FRHM are CHM (Fisher et al 2004) (Parry et al 2011, Reddy et al 2013. For women with NLRP7 mutations who wish to achieve a normal pregnancy, in vitro fertilization with ovum donation has been shown to provide a viable option (Fisher et al 2011, Akoury et al 2015b It has recently been suggested that heterozygous mutations in NLRP7 may be associated with other forms of reproductive failure other than BiHM, such as recurrent miscarriage and sporadic CHM (Messaed et al 2011).…”
Section: Other Pregnancy Outcomes Associated With Nlrp7 Maternal-effementioning
confidence: 99%
“…To date, most mutations in KHDC3L have been found to be small deletions, with two variants affecting the initiation codon and a single variant giving rise to a splice site mutation (Parry et al 2011, Reddy et al 2013.…”
Section: Biparental Hydatidiform Molesmentioning
confidence: 99%